Total synthesis of depudecin and analogues via an olefin cross-metathesis based strategy - Cheng-Sánchez, Iván; Sarabia-García, Francisco Ramón (My University, 2017)
(-)-Depudecin (1), isolated from the culture broths of the fungus Alternaria brassicicola [1], has been identified as a selective inhibitor of histone deacetylases (HDAC) with an IC50 in the low μM range. In contrast to representative HDAC inhibitors, depudecin represents a unique inhibitor of these enzymes by virtue of its molecular structure, featuring the presence of two oxirane rings separated by a trans double bond. Originally discovered as part of a biological screen directed towards the identification of antitumour agents with detransforming activity [2], depudecin was identified as a bioactive metabolite capable of reverting the transformed morphology of tumor cells. Depudecin induced cell cycle arrest and cellular differentiation [3], and also exhibited anti-angiogenesis activity [4]. Prompted by its striking biological properties and enticing structure, we decided to initiate a research program directed towards the synthesis of natural depudecin which has recently culminated with a linear total synthesis [5]. In order to develop an improved access to natural depudecin and analogues for further biological screenings, we explored a synthetic alternative as a shorter and more convergent approach. In this communication we report a new total synthesis of the natural product (-)-depudecin. A key feature of the synthesis is the utilization of an olefin cross-metathesis strategy, which provides for an efficient and improved access to natural depudecin. This strategy was applied to the preparation of the 10-epi and (+)-depudecin, which represent interesting stereoisomeric analogues for SAR studies.
Keywords: Antineoplásicos; Total synthesis; Natural products; Antitumor Agents; Depudecin